Criterios urbanos para espacios públicos desde la perspectiva de una persona con discapacidad auditiva - Montaño Pezo, Rebeca Dennisse (2024)
This work proposes the planning and design of public spaces within the urban environment to ensure accessibility and quality of life for all citizens, including people with hearing disabilities. The proposal establishes specific urban criteria for a route or section of the city from the perspective of a person with various limitations, applying cultural and social factors of our local reality. These spaces are essential for social interaction and inclusion, without sensory and communicational barriers, allowing for successful social cohesion. The project takes an integrative approach that prioritizes accessibility and the effective and user-friendly flow of movement. It highlights the importance and strategy of implementing clear visual signage, accessible routes, reducing limiting obstacles, and incorporating urban furniture that facilitates visual and non-verbal communication. Its execution was based on an exhaustive study of the site and its surroundings, using qualitative and quantitative data collection techniques. The result is to provide an option for the urban environment that is not only functional and aesthetically pleasing but also fosters a sense of belonging and safety for all users, transforming underutilized spaces into inclusive, accessible, and welcoming areas that promote the full participation of all inhabitants in community life. The inclusive sensory experience incorporates elements that consider limitations, including, among others, the installation of clear vertical and horizontal visual signage, tactile flooring, the creation of barrier-free accessible routes, ramps, and urban furniture designed to enhance non-verbal communication.